Penulisan Karya Ilmiah sebagai Salah Satu Tools Meningkatkan Kemampuan Berpikir Kritis - R. Hariyani Susanti (Universitas Adiwangsa Jambi, 2023)
Writing scientific papers is one way to improve critical thinking skills. In an era of increasingly developing information, critical thinking skills are needed to obtain accurate and valid information. The purpose of this study is to determine how writing scientific papers can improve critical thinking skills. The research method used is a literature study using various sources related to scientific writing and critical thinking skills. The results of the study show that writing scientific papers can improve critical thinking skills because it involves the process of data collection, data analysis, and problem-solving. In addition, writing scientific papers also trains the ability to select relevant and valid information, as well as draw conclusions based on existing facts. However, writing scientific papers also has challenges that must be faced, such as difficulties in organizing information, writing systematically, and paying attention to grammar. Therefore, special training is needed to improve scientific writing skills in order to improve critical thinking skills.